Have cap, will travel U.S. nurses abroad 1898-1917 - Connerton, Winifred C. (ProQuest LLC, 2010)
This history of American nurses in the Philippines and Puerto Rico from 1898 to 1917 connects American internationalism with professional nursing. Nurses' work with the Army, colonial governments and mission hospitals was integral to American internationalism of this period. Nurses' work abroad also influenced the profession within the U.S. The study of American nurses in U.S. colonies offers a rich opportunity for analysis of women's roles in colonial expansion, construction of racial identities, and grassroots participation in national projects, in the histories of the colonial Philippines and Puerto Rico and of nursing professional development. By 1898 trained nursing was accepted as a component of proper American health care. During the Spanish-American War the American public demanded nursing care for soldiers. Similarly, the colonial governments of the Philippines and Puerto Rico provided American trained nurses in colonial hospitals as a benefit for colonial workers. This was a significant development for the nursing profession - running a colonial or military health care service without the skills of trained nurses was no longer possible. The profession of trained nursing was entwined with American colonial governments' goals in the colonies. The colonial governments promoted nursing skills as essential to self-governance. Native trained nurses would minister to their countrymen and demonstrate proper sanitation and health practices that would also promote healthy democracy and civic functioning. Protestant missionaries also expected that native nurses trained in the mission schools would offer health care to their communities while evangelizing. Although the actual number of nurses who worked abroad in this period was small, they had a disproportionate impact on the domestic profession.--Abstract.